Whoosh and Chug! - Braun, Sébastien (Harper / HarperCollins, 2014)
"Some trains may think fast is best, but only slow and steady Chug can save the day"--
"Originally published in Great Britain by HarperCollins Children's Books in 2012"--Copyright page
Keywords: Railroad trains / Fiction; Safety / Fiction; Friendship / Fiction